What factors empower general practitioners for early cancer diagnosis? A 20-country european delphi study - ÇİFÇİLİ, SALİHA SERAP (My University, 2022)
BACKGROUND: Some symptoms are recognised as red flags for cancer, causing the General Practitioner (GP) to refer the patient for investigation without delay. However, many early symptoms of cancer are vague and unspecific, and in these cases, a delay in referral risks a diagnosis of cancer that is too late. Empowering GPs in their management of patients that may have cancer is likely to lead to more timely cancer diagnoses. AIM: To identify the factors that affect European GPs\" empowerment in making an early diagnosis of cancer. METHODS: This was a Delphi study involving GPs in 20 European countries. We presented GPs with 52 statements representing factors that could empower GPs to increase the number of early cancer diagnoses. Over three Delphi rounds, we asked GPs to indicate the clinical relevance of each statement on a Likert scale.The final list of statements indicated those that were considered by consensus to be the most relevant. RESULTS: In total, 53 GPs from 20 European countries completed the Delphi process, out of the 68 GPs who completed round one. Twelve statements satisfied the pre-defined criteria for relevance. Five of the statements related to screening and four to the primary/secondary care interface. The other selected statements concerned information technology (IT) and GPs\" working conditions. Statements relating to training, skills and working efficiency were not considered priority areas. CONCLUSION: GPs consider that system factors relating to screening, the primary-secondary care interface, IT and their working conditions are key to enhancing their empowerment in patients that could have cancer. These findings provide the basis for seeking actions and policies that will support GPs in their efforts to achieve timely cancer diagnosis.
Keywords: Tıp; Dahili Tıp Bilimleri; Aile Hekimliği; Sosyal ve Beşeri Bilimler; Sosyoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Family Medicine; Social Sciences and Humanities; Sociology; Health Sciences; Klinik Tıp (MED); Sosyal Bilimler (SOC); Klinik Tıp; Sosyal Bilimler Genel; SAĞLIK BAKIM BİLİMLERİ VE HİZMETLERİ; KAMU, ÇEVRE VE İŞ SAĞLIĞI; Clinical Medicine (MED); Social Sciences (SOC); CLINICAL MEDICINE; SOCIAL SCIENCES, GENERAL; HEALTH CARE SCIENCES & SERVICES; PUBLIC, ENVIRONMENTAL & OCCUPATIONAL HEALTH; Halk, Çevre ve İş Sağlığı; Bakım Planlaması; Public Health, Environmental and Occupational Health; Care Planning; cancer; Delphi method; empowerment; general practitioners; Primary Health Care; cancer; Delphi method; empowerment; general practitioners; Primary Health Care